PraPon wrote:

x > y?

(1) \(\frac{x}{2} = y-3\)

\(x = 2y - 6\)

If x = 0 then y = 3. Thus x < y

If x = -2 then y = -4. Thus x > y

Hence INSUFFICIENT

(2) \(y > 6\)

Clearly INSUFFICIENT

Combine (1) & (2)

Substitute inequality from statement (1) x = 2y - 6 into the question

\(x>y?\)

i.e \(2y-6>y?\)

i.e. \(y > 6?\) YES, this is our statement(2).

- SUFFICIENT.

Hence choice(C) is the answer.

small calc. mistake in the highlighted position I think. when x=-2 then y = 2 NOT -4 as you have mistakenly shown hence in this case too x<y

to show A is insuff. if we take y= 5 then we get x= 4 and y>x

if y=6 then we get x=6 here x=y if y =7 and x=8 here x>y

hence A is insuff.

B is insuff. because no info for x.

1+2 together

if y >6 then of course x>y

_________________

- Stne